Urban greenspace and neighborhood crime - Wo, James C. (Criminology, 2024)
Urban greenspace (UGS) has been recently linked to public safety. Criminologists, however, have been largely absent from the discussion about this association, despite having important theoretical tools and empirical findings to contribute. In the current study, we review the prominent criminological perspectives that may be used to explain the association between UGS and crime. Furthermore, we draw from prior work to extend beyond the question of whether UGS affects crime to the more crucial question of when it does. Using a sample of block groups in Washington, D.C., we examine the association between two measures of UGS—tree canopy coverage and noncanopy vegetation coverage—and violent and property crime. We also assess the moderating effects of antecedents to social disorganization (poverty and homeownership) on the association between UGS and crime. Our results suggest that both types of UGS are associated with fewer crimes, even while controlling for a range of criminogenic factors. The effects of tree canopy coverage appear to be crime general, while the effects of noncanopy vegetation coverage only apply to violent crime. The effects of tree canopy, however, are weaker in communities characterized by high levels of poverty and low levels of homeownership.